Policy principles for sustainable and just land systems - Rachael Garrett; Patrick Meyfroidt; Ariane de Bremond; Ariani Wartenberg; Lindsay Barbieri; Álvaro Fernández-Llamazares; Emmanuel Acheampong; Thomas Addoah; Matthew Adeleye; Peter Alexander; Joyce Brand\~ao; David Anthony Coomes; et al. (Royal Society Open Science, 2025)
Land systems are the nexus of many global sustainability and justice challenges. Here we present eight guiding principles (P1-8) for improved land system policies following the heuristic stages of a policy cycle. The principles are as follows: embrace recognitional justice (P1), be politically strategic (P2), consider multiple policy goals (P3), address systemic issues (P4), take an integrative scope (P5), foster co-development (P6), adopt clear and monitorable targets (P7) and integrate diagnostic and adaptive capacities (P8). We then explore how well policies align with these principles in two globally relevant cases (land-based climate mitigation and biodiversity-friendly agriculture). In both cases, we find that when policies align poorly with the principles at the agenda-setting stage, there is further misalignment at the policy formulation stage. In the instances when recognitional justice is embraced at the onset, policies subsequently integrate more diverse goals and co-development, but they insufficiently consider political strategy and struggle to handle system complexity. Nonetheless, we identify promising policy mixes that provide benefits to multiple actors, integrate multiple goals, take an integrative scope and have strong monitoring and adaptation, aligning well with multiple principles. Further investigation of these principles could reveal promising policy pathways for land systems.
Keywords: 630; governance; science-policy; sustainability transitions; conservation; climate; food; transformation